Quality of Final Diagnosis Coding in the Medical Records of Selected Hospitals in the Colombo District, Sri Lanka - Gamage, U.S.H. (Health information management : journal of the Health Information Management Association of Australia, 2004)
Clinical coding is a method of translating a clinical description of a disease or procedure into a standard code. Sri Lanka adopted the system of coding recommended by the WHO, The International Classification of Diseases – 10th Revision (ICD-10), in 1997, and this study was undertaken with the objectives of assessing the quality of ICD coding and to identify some factors influencing coding quality in this country. A sample of 1091 medical records was selected from six hospitals in the Colombo District, representing all categories of hospitals in the area. Quality of coding was assessed by using the Australian Coding Benchmark Audit (ACBA), a coding quality assessment tool developed by the National Centre for Classification in Health, Australia. It was found that the availability of the final diagnosis on front sheets of medical records was satisfactory (94.7%), but the accuracy of the diagnostic statement was unsatisfactory (54%). Out of the six hospitals studied, only the Teaching Hospital and the Peripheral Unit practiced coding. The overall rate of accuracy of ICD coding in the Colombo District hospitals was 31%, which is unsatisfactory. It is recommended that training opportunities in ICD-10 and other related subjects should be made available to the coders. Efforts should be made to improve the familiarity of the Medical Officers with the WHO guidelines on recording diagnostic information for ICD coding.